2022
DOI: 10.3390/vaccines10020329
|View full text |Cite
|
Sign up to set email alerts
|

Is Mandatory Vaccination in Population over 60 Adequate to Control the COVID-19 Pandemic in E.U.?

Abstract: Vaccine hesitancy, which potentially leads to the refusal or delayed acceptance of COVID-19 vaccines, is considered a key driver of the increasing death toll from the pandemic in the EU. The European Commission and several member states’ governments are either planning or have already directly or indirectly announced mandatory vaccination for individuals aged over 60, the group which has repeatedly proved to be the most vulnerable. In this paper, an assessment of this strategy’s benefits is attempted by derivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The present work shows the great importance of vaccination not only to prevent hospitalization of infected people, but also to reduce deaths in agreement with published evidences (Machado et al 2022, Hulíková Tesárková and Dzúrová 2022, Rachaniotis et al 2022: the maximum number of deaths and years of life lost occurs during the period without mandatory vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…The present work shows the great importance of vaccination not only to prevent hospitalization of infected people, but also to reduce deaths in agreement with published evidences (Machado et al 2022, Hulíková Tesárková and Dzúrová 2022, Rachaniotis et al 2022: the maximum number of deaths and years of life lost occurs during the period without mandatory vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…The issue of COVID-19 vaccination nevertheless remains a controversial subject for the public, and among physicians [ 37 , 39 , 40 ]. As previously mentioned, after vaccine rollout, several countries implemented some form of vaccine incentive, either as a green pass, or as a fine for non-vaccinated individuals [ 28 , 29 ]. A study in the elderly population in southern Italy showed that after the green pass adoption, fewer people supported the vaccine mandate [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the vaccination campaign, vaccine hesitancy has been a reason for public discussion and social reactions for many countries globally and especially across Europe [ 27 ]. Therefore, many European countries made decisions about vaccine incentives for compliant groups, in the form of green passes, or penalties for non-compliant ones, such as fines for non-vaccination [ 28 ]. This sparked deviating opinions, with many people rejecting the option of mandatory vaccination, regardless of their vaccination status [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, vaccine effectiveness against symptomatic Omicron infection was reduced, even in the highly vaccinated department’s population. Current vaccines are protecting against severe illness, hospitalization, and death [ 3 ], but Omicron transmission is clearly possible among both vaccinated and unvaccinated individuals, partially evading immunity acquired from prior COVID-19 infection and from a two or three dose mRNA vaccine regimen [ 15 ]. This was observed in the department, especially after the advent of Omicron variant BA.5.…”
Section: Discussionmentioning
confidence: 99%
“…Up to December 2020, due to the absence of effective therapies and vaccines, the Greek government options were limited to non-pharmaceutical interventions (NPIs) to deter viral transmission, minimize death rates, and resume normal activities. They included, inter alia, social distancing and lockdowns, travel restrictions, face-masks, teleworking, contact tracing, isolation/quarantine, and school/university closures [ 3 ].…”
Section: Introductionmentioning
confidence: 99%